Theoretical System Dynamics Modeling for Taiwan Pediatric Workforce in an Era of National Health Insurance and Low Birth Rates - Mei-Hwan Wu; Jiun-Yu Yu; Chung-Hsing Huang (Elsevier, 2013)
In an era of declining birth rates and a single-payer health care system, the pediatric workforce might overreact to its demands. System dynamics (SD) were therefore applied to establish models to predict the future need and demand for the pediatric workforce. Materials and methods: Data of population and workforce were extracted from national databases and models developed using Vensim software. Results: In the past decade, the child-to-pediatrician ratio correlated with infant mortality in Taiwan (p < 0.001, r2 = 0.88, child-to-pediatrician ratio = 146 + 354 × infant mortality/1000 live births). Currently, the child-to-pediatrician ratio is 1742:1. Using the Millennium Development Goals (2.437/1000 live births) for infant mortality, the child-to-pediatrician ratio was estimated as 1009:1. The pediatric population model incorporated the birth and mortality rates in each age category, accurately predicted population changes between 1974 and 2010, and projected a decreasing trend until 2017. The pediatric workforce model, which considered rates of enrollment, completion, certification, and retention, predicted a decrease in the supply of pediatricians in the mid-2010s that could be delayed by policy incentives. When targeting the base scenario, the model indicated that discrepancies between demands and supply of pediatricians would occur in the late 2010s toward 2020. When targeting the Millennium Development Goals scenario, however, the discrepancies would be consistent. Conclusion: Effective SD models were developed for the population and health care workforce. The strengths of the SD models are derived from simulation, which is subject to influence from new policies. Policies can, therefore, be examined and intervened in a timely manner.